VD_FINDINFO AP / 2011 / 124 vom 11. März 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, RÉSILIATION, CONDITIONS GÉNÉRALES DU CONTRAT, PRINCIPE DE LA BONNE FOI, INTÉRÊT MORATOIRE | 8 CC, 1 CO, 102 CO, 104 CO, 18 CO, 456a CPC